The Role of BPIP in Indonesia’s Legal Reform: Navigating Social Transformation and Ideology Education Challenges - Fuad Lutfi; Suwito Eko Pramono; Masrukhi Masrukhi (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
The Pancasila Ideology Development Agency (Badan Pembinaan Ideologi Pancasila, BPIP) plays a pivotal role in Indonesia’s ongoing legal reform, acting as a vital institution in promoting Pancasila—the nation’s foundational ideology. This research explores the significance of BPIP in navigating the intricate nexus between legal reform, social transformation, and ideology education. The urgency of this study stems from the pressing need to address challenges posed by globalization, which often undermines Indonesia’s ideological values, and the growing demand for a legal system aligned with Pancasila principles. By employing a socio-legal approach, this study examines BPIP’s functions, legal framework, and effectiveness in fostering ideological integrity while accommodating diverse societal transformations. The novelty of this research lies in its comprehensive analysis of BPIP’s strategic role in aligning legal reforms with Pancasila-based values. It highlights the institution's contribution to addressing ideological fragmentation and its potential to bridge the gap between constitutional ideals and societal realities. Moreover, the study underscores the importance of integrating ideology education with legal reform efforts to ensure sustainability and inclusivity. The findings provide a critical evaluation of BPIP’s impact on Indonesia’s legal development and propose actionable strategies to enhance its role in shaping a transformative and ideology-driven legal framework. This research contributes to the broader discourse on legal reform by offering a unique perspective on the interplay between ideology and law, serving as a reference for policymakers and scholars seeking to strengthen Indonesia’s legal and ideological foundations.